Crystalline ruthenium polypyridine nanoparticles: a targeted treatment of bacterial infection with multifunctional antibacterial, adhesion and surface-anchoring photosensitizer properties. Issue 18 (9th April 2021) - Yin, Chenyang; Wang, Zekun; Ding, Xiaoyuan; Chen, Xiaoqing; Wang, Jingyuan; Yang, Endong; Wang, Weiyun; Martin, Lisandra L; Sun, Dongdong
Abstract : Sph-Ru-MMT@PZ adheres to cell surfaces via sticky montmorillonite. Irradiation therapy generates reactive oxygen species that lyse E. coli, emitting an intense red fluorescence giving rapid feedback on the efficacy of antibacterial treatments. Abstract : Photodynamic antibacterial therapy employs nanocomposites as an alternative to traditional antibiotics for the treatment of bacterial infections. However, many of these antibacterial materials are less effective towards bacteria than traditional drugs, either due to poor specificity or antibacterial activity. This can result in needless and excessive drug use in treatments. This paper describes a multifunctional drug delivery nanoparticle (MDD-NP), Sph-Ru-MMT@PZ, based on the nanostructured-form of [Ru(bpy)2 dppz] (PF6 )2 (Sph-Ru), which has adhesive properties towards its microbial targets as well as surface-anchoring photosensitizer effects. The design and construction of MDD-NP is based on the adhesive properties of the outer layers of montmorillonite (MMT), which allows Sph-Ru-MMT@PZ to successfully reach its bacterial target; the outer layer of the E. coli . In addition, under 670 nm red irradiation therapy (R-IT), the surface-anchoring properties use the photosensitizer phthalocyanine zinc (PZ) to destroy the bacteria by producing reactive oxygen species (ROS) which causes cell lysis of E. coli . More importantly, Sph-Ru-MMT@PZ has no fluorescence response to live E. coli with intact cell membranes but selectively stained and demonstrated fluorescence during membrane damage of early-stage cells as well as exposure of nuclear materials at late-stage of cell lysis. Sph-Ru-MMT@PZ showed beneficial and synergistic anti-infective effects in vivo by inhibiting the E. coli infection-induced inflammatory response and eventually promoting wound healing in mice. This new strategy for high precision antibacterial therapy towards specific targets, provides an exciting opportunity for the application of multifunctional nanocomposites towards microbial infections.